PENGARUH PENAMBAHAN IRANIAN ENDURANCE EXERCISE PADA NTERVENSI SHORT WAVE DIATHERMY DALAM MENGURANGI NYERI PINGGANG KRONIK - Kurniaji, Noor; kurniaji, noor (Universitas Muhammadiyah Surakarta, 2008)
Back pain is a case that commonly found in physiotherapy clinical practice. Back pain causesimmobility which reduce the ability and function ofÂ pelvic motion. One of them is reduction in endurance ofpelvis stabilization muscle. Iranian endurance exercise is an exercise that is applicable to solve suchproblem. Population for this study is all persons who suffered from pelvis pain which getting SWDintervention in Physiotherapy Installation Prof Soeharso Hospital. Samples for this study consist of 14persons. The data achieved were tested using Wilcoxon signed rank test. It was found that SWD (p=0.017)and SWD + Iranian Endurance Exercise (p=0.018) had potent to reduce chronically pelvis pain. Difference inmean pain reduction between both groups showed that SWD + IEE group (4.86) experienced more painreduction compared to SWD group (3.43). However, Mann-whitney test revealed that there was nosignificant difference between both groups (p=0.087). Therefore, Iranian Endurance Exercise, combined with